Structural analysis of some pre-Cape formations in the Western Province - Hartnady, Christopher John Hubert (Department of Geological Sciences, 2021)
The principal objective of the present study was the testing of previous stratigraphic interpretations, particularly in respect of the Klipheuwel and Franschhoek formations, by means of attention to hitherto generally neglected structural or tectonic aspects of the pre-Cape rocks. In the Worcester area, it was found that the structural sequence across the so-called Malmesbury-Klipheuwel unconformity (de Villiers, Jansen and Mulder, 1964) is the reverse of that previously postulated, and the controversial correlation of the lower (previously upper) formation with the Klipheuwel Group cannot be maintained. The deformation of the pre-Cape formations is considered to have taken place in four stages or phases, labelled 0, M, X and K in sequence. The Early phases, 0 and M, are responsible for the broad stratigraphic pattern, while the Late phases, X and K, locally modify the earlier structures and have little or no effect on the distribution of rock types. An important tectonic discontinuity, or slide, apparently separates the upper formation from the two lower units, and close to the much younger Worcester Fault, a pre-Cape thrust has brought sheared and mylonitised granitic rocks to rest against the former. Structural relationships at Franschhoek are confusing, but in Kaaimansgat structures of Early and Late generations can be distinguished. In these southern areas the deformation of the rocks is again such that they clearly cannot be correlated with the Klipheuwel Group. However, their close association with older, sheared granitoid rocks and caraclasites - one of the main points upon which the Franschhoek-Klipheuwel correlation was based - is not in dispute. Although granite studies were not included in the scope of this work, one of the incidental results has been to widen the field of the older granite problem to include Kaaimansgat and Worcester as well as Franschhoek. The relationships of the pre-Cape formations treated in this work - called the Boland Group (after Rabie, 1948) - to the "Malmesbury" formations farther west is still problematical. The deformation of most of the pre-Cape formations in the Western Cape Province, Boland and "Malmesbury" alike, was apparently effected during a major orogenic event in upper Proterozoic - lower Paleozoic times. The term "Saldanian" is proposed as generally descriptive of this event and the structures which it has produced.